Interaction between blood cadmium and lead concentration and physical activity on hypertension from the Korean national health and nutrition examination survey in 2008-2013 - Jeoung A Kwon; Byungmi Kim; Eunji Kim; Kisung Kwon (BMC, 2023)
Abstract Background Previous studies have suggested that blood Cd, Pb exposure, and physical activity levels may influence the development of hypertension. This study aimed to investigate the relationship between blood Cd, Pb levels, and hypertension by the level of physical activity in Korean adults using The Korea National Health and Nutrition Examination Survey (KNHANES). Methods We used data from the KNHANES (2008-2013), a nationally representative, cross-sectional, population-based study. We included 8,510 participants who had records of blood Cd, Pb and, blood pressure measurements. Multiple logistic regression was used to examine the association between blood Cd and Pb exposure and the development of hypertension, as well as the modifying effects of physical activity levels. Additive interaction was estimated using relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP) and synergy index (S). Results Following covariates adjustments, we found significant associations of blood Cd and Pb with higher hypertension prevalence. This association was more apparent in low physical activity while blood Cd and Pb concentrations were not significantly associated with hypertension in participants with more activity. Additionally, there was a significant interaction between blood Cd and physical activity on hypertension risk (RERI = 0.17, 95% CI: -0.36-0.7; AP = 0.12, 95% CI: -0.28-0.52; S = 1.75, 95% CI:1.36-2.14). Conclusions Our results suggest that low physical activity may substantially amplify the adverse effects of blood Pb and Cd exposure on hypertension risk. However, interactions were only found for Cd. Further studies are needed to confirm these findings.